Academic Self-Efficacy Muhammadiyah University Students Sidoarjo Faculty Of Business Law And Social Science: Efikasi Diri Akademik Mahasiswa Universitas Muhammadiyah Sidoarjo Fakultas Bisnis Hukum Dan Ilmu Sosial - Tri Sulistiono; Ghozali Rusyid Affandi (Academia Open, 2021)
This research is motivated by the phenomenon of students who lack academic self-efficacy in undergoing the process of academic activities at Muhammadiyah University of Sidoarjo. This study aims to determine the academic self-efficacy of the students of the Faculty of Business, Law and Social Sciences, Muhammadiyah University of Sidoarjo. The method used in this research is descriptive quantitative. The variable contained in this study is academic self-efficacy. This research was conducted at the University of Muhammadiyah Sidoarjo using students for the Academic Year 2020-2021 as many as 320 student subjects taken using the proportional sampling technique. The data collection technique in this study used an academic self-efficacy scale with a Likert-scaled model. Data analysis was carried out by descriptive statistical analysis with categorization techniques. The results of data analysis showed that most of the students' academic self-efficacy levels were in the medium category (71%), a few were in the low category (16%), but a small portion had high self-efficacy (13%),. The study programs that have are Management study programs with an average score of 70.70, and Law study programs are 70.43. While the highest aspect is generality with an average value of 26.45, magnitude 25.13, strength aspect 18.48.